2021
DOI: 10.3390/ijerph18116011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Central Discharge Element Sock for Plantar Temperature Reduction and Improving Comfort

Abstract: U-shaped plantar cushions could help reduce stress affecting the central forefoot without the need for an orthosis, but they are yet to be integrated as an element in socks. The objective of this study was to verify the effectiveness of a sock with a central discharge element in terms of plantar temperature and comfort. The sample comprised 38 subjects (13 men and 25 women). Their plantar temperatures were measured with a thermographic camera in a basal situation and after each of two 10-minute walks around an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The measurement conditions, the type of terrain, the distance run, or the intensity of the exercise will condition the increase in temperature of the body in general and the soles of the feet in particular. Thus, Reddy et al [9] found that foot temperature increased by 4.6°C after 45 minutes of walking, and Martínez Nova et al [13] found increases of 3°C after 10 minutes of walking at an easy pace. Because of all the above, the thermoregulatory effect provided by the socks studied allows the foot temperature to be maintained in ranges similar to those generated by a low intensity physical activity, thus being effective in their mission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement conditions, the type of terrain, the distance run, or the intensity of the exercise will condition the increase in temperature of the body in general and the soles of the feet in particular. Thus, Reddy et al [9] found that foot temperature increased by 4.6°C after 45 minutes of walking, and Martínez Nova et al [13] found increases of 3°C after 10 minutes of walking at an easy pace. Because of all the above, the thermoregulatory effect provided by the socks studied allows the foot temperature to be maintained in ranges similar to those generated by a low intensity physical activity, thus being effective in their mission.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three-dimensional plantar elements have been incorporated that have shown to reduce the temperature [13] and plantar pressure on the central forefoot [14,15]. There are currently on the market socks with rib-shaped elements that have different separations between the waves.…”
Section: Introductionmentioning
confidence: 99%
“…By keeping the feet cooler and drier, friction is minimized and excessive moisture is avoided, contributing to the prevention of skin injuries. The textile industry has a major challenge here since the specific design of the sock planting area, which has shown beneficial effects in reducing zonal temperature [ 29 ] or dynamic plantar pressure [ 11 ], could improve comfort and performance in racing with such an important physical demand.…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of this study is linked to the development of a moldable thermoregulatory epoxy resin for the development of orthopedic insoles that support both heel and foot arch. A major disadvantage of orthopedic insoles, which deters their use among some patients, is the significantly higher in-shoe temperature, affecting other relevant variables such as perspiration [ 20 ] and fungal infection. In Figure 1 (left), a schematic representation of thermal energy flows is presented.…”
Section: Introductionmentioning
confidence: 99%